Efficient Production of Phosphorene Nanosheets via Shear Stress Mediated Exfoliation for Low‐Temperature Perovskite Solar Cells. Issue 5 (8th February 2019) - Batmunkh, Munkhbayar; Vimalanathan, Kasturi; Wu, Congcong; Bati, Abdulaziz S. R.; Yu, LePing; Tawfik, Sherif Abdulkader; Ford, Michael J.; Macdonald, Thomas J.; Raston, Colin L.; Priya, Shashank; Gibson, Christopher T.; Shapter, Joseph G.
Abstract: A simple and fast "top‐down" protocol is introduced herein to prepare solution processable few‐layer phosphorene nanosheets using vortex fluidic mediated exfoliation under near‐infrared (NIR) pulsed laser irradiation. This novel shear‐exfoliation method requires short processing times and produces highly crystalline, atomically thin phosphorene nanosheets (4.3 ± 0.4 nm). The as‐prepared phosphorene nanosheets are used as an effective electron transporting material (ETM) for low‐temperature processed, planar n‐i‐p perovskite solar cells (PSCs). With the addition of phosphorene, the average power conversion efficiency (PCE) increases from 14.32% to 16.53% with a maximum PCE of 17.85% observed for the phosphorene incorporated PSCs which is comparable to the devices made using the traditional high‐temperature protocol. Experimental and theoretical (density‐functional theory) investigations reveal the PCE improvements are due to the high carrier mobility and suitable band energy alignment of the phosphorene. The work not only paves the way for novel synthesis of 2D materials, but also opens a new avenue in using phosphorene as an efficient ETM in photovoltaic devices. Abstract : Solution processable few‐layer phosphorene nanosheets are prepared based on simple and fast "top‐down" protocol using vortex fluidic mediated exfoliation under NIR pulsed laser irradiation and used as an effective electron transporting material for low‐temperature processed perovskite solar cells.